1979
DOI: 10.1002/app.1979.070230106
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of kevlar 49 fiber

Abstract: The high‐strength, high‐modulus Kevlar 49 fiber is widely used today because of its superior properties. In this paper, we discuss the fundamental physicochemical nature of the commercial fiber. It is an extended chain polymer, poly(p‐phenylene terephthalamide), which is highly crystalline. Extensive analysis shows that the material composition is quite consistent from lot to lot and is low in impurities. The fiber absorbs water reversibly; the extent of absorption is related to the ash content. The well‐known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
3

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(71 citation statements)
references
References 10 publications
2
66
0
3
Order By: Relevance
“…In the case of Na 2 SO 4 , it has been shown that it is present in Kevlar TM 49 ÿbres at concentrations of up to 1:5 wt% (Morgan and Pruneda, 1987), located predominantly between 60 nm microÿbrils within the ÿbre. While Penn and Table 2 Equilibrium moisture sorption characteristics of Kevlar TM aramid ÿbres (Fukuda et al, 1991) Larsen (1979) showed a direct correlation between sample 'ash' (inorganic component) content and equilibrium moisture content, more recent work conducted by Fukuda et al (1991) has shown no such correlation. Indeed, samples boiled for 30 days (in the process losing up to 50% of the sodium salt) showed no change in equilibrium moisture content compared to those of untreated samples.…”
Section: Introductionmentioning
confidence: 91%
“…In the case of Na 2 SO 4 , it has been shown that it is present in Kevlar TM 49 ÿbres at concentrations of up to 1:5 wt% (Morgan and Pruneda, 1987), located predominantly between 60 nm microÿbrils within the ÿbre. While Penn and Table 2 Equilibrium moisture sorption characteristics of Kevlar TM aramid ÿbres (Fukuda et al, 1991) Larsen (1979) showed a direct correlation between sample 'ash' (inorganic component) content and equilibrium moisture content, more recent work conducted by Fukuda et al (1991) has shown no such correlation. Indeed, samples boiled for 30 days (in the process losing up to 50% of the sodium salt) showed no change in equilibrium moisture content compared to those of untreated samples.…”
Section: Introductionmentioning
confidence: 91%
“…However, there are some weak reflections that do not obey the space group extinction law, as mentioned by Penn and Larsen (26).…”
Section: Meridional Diffractionmentioning
confidence: 97%
“…The spectra of the polymer matrix-coated Kevlar cloth were obtained by the internal reflection spectroscopy (IRS) on 45" germanium element. 5 The coating of Kevlar cloth was made with 0.05% polymer solution in dichloromethane and the solvent was completely removed in a vacuum oven. The spectra of the mixture of polymer matrix with B were obtained by the transmission method on a sample film coated onto potassium bromide window.…”
Section: Measurementsmentioning
confidence: 99%